Spatio-temporal diversity and genetic architecture of pyrantel resistance in Cylicocyclus nassatus, the most abundant horse parasite - Sallé, Guillaume; Courtot, Élise; Cabau, Cédric; Parrinello, Hugues; Serreau, Delphine; Reigner, Fabrice; Gesbert, Amandine; Jacquinot, Lauriane; Lenhof, Océane; Aimé, Annabelle; Picandet, Valérie; Kuzmina, Tetiana; et al. (Peer Community Journal, 2025)

(untitled)
Cyathostomins are a complex of 50 intestinal parasite species infecting horses and wild equids. The massive administration of modern anthelmintic drugs has increased their relative abundance in horse helminth communities and selected drug-resistant isolates worldwide. Cylicocyclus nassatus is the most prevalent and the most abundant species. The tedious identification and isolation of these worms have hampered studies of their biology that remain largely uncharacterised. Here we have leveraged ultra-low input sequencing protocols to build a reference genome for the most prevalent horse strongyle species. Using this resource, we have established the first estimates of its genetic diversity and population structure on a gradient ranging from Ukraine (close to modern horse domestication area) to North America, while capturing a 19th-century snapshot of C. nassatus diversity in Egypt. Our results support a diverse and lowly structured global population. Modern populations displayed lower nucleotide diversity relative to the old North African isolate. We identified the first genetic candidates upon which pyrantel (an anthelmintic drug used in companion animals) selection likely applied in field populations, highlighting previously suspected genes coding for nicotinic acetylcholine receptor subunits, and identifying new candidates showing differential expression in independently evolved Caenorhabditis elegans lines. These results offer a first resource to widen current knowledge on cyathostomin biology, unravel novel aspects of pyrantel resistance mechanisms and provide candidate genes to track pyrantel resistance in the field.